The concept of futility in health: A scoping review. (December 2021) - da Silva Vieira, João Vítor; Deodato, Sérgio; Mendes, Felismina
Introduction: Due to the constant scientific and technological development, health professionals are regularly confronted with situations in which there are always therapeutic options, regardless of the severity of the patient's condition. However, regarding these therapeutic options as feasible in all situations can be harmful, since it is universally accepted that, despite all advances in health, there are inevitable limits and the promotion of some interventions may be useless or futile. Objective: To characterize the use of the concept of futility in the health literature. Method: Review of the literature following the Scoping Review protocol of the Joanna Briggs Institute. The research was performed in CINAHL, Cochrane, Pubmed, Scopus e Web of Science to identify studies published prior to 2020. Nineteen studies were selected. Results: There is no universally accepted definition for the concept of futility. In the literature there are different conceptions for the concept of futility that point to qualitative and quantitative roots and that are associated with ethical dilemmas that make it difficult to conceptualize this concept and make it operational in clinical practice. Conclusion: The central elements of the concept of futility include: the diagnosis of futility is closely related to clinical judgment; futility has both quantitative and qualitative roots; futility is always appreciated posteriori; futility is related to the lack of benefit. It is essential to promote a discussion that enables the definition of the concept and that makes it possible to promote ethical principles in care, especially when the inevitable limits of treatments are reached.